Analisis Pengaruh Keunggulan Produk Simpanan Sukarela, Pelayanan dan Promosi terhadap Minat Bergabung sebagai Anggota di KSPPS BMT NU Jombang Cabang Kesamben - Wijayanti, Lulud; Saiful , Mohamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2024)
This study aims to analyze the influence of the advantages of the Voluntary Savings product, service quality, and promotion on the interest in becoming a member of KSPPS BMT NU Jombang, Kesamben Branch. In facing the increasingly fierce competition among financial institutions, KSPPS BMT NU Jombang needs to develop appropriate strategies to attract and retain members. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to prospective members and analyzed using the t-test to examine the partial influence and the F-test to evaluate the simultaneous effect. The results of the study indicate that, partially, the promotion variable does not have a significant effect on the interest in becoming a member. However, the advantages of the Voluntary Savings product and service quality have a significant influence. Simultaneously, all three variables (Voluntary Savings product advantages, service quality, and promotion) significantly affect the public's interest in becoming members. This research is expected to provide valuable insights for KSPPS BMT NU Jombang in enhancing marketing and service strategies, as well as contributing to the development of Islamic financial institutions